Enhanced Expression of Pullulanase in Bacillus subtilis by New Strong Promoters Mined From Transcriptome Data, Both Alone and in Combination - Meng, Fanqiang; Zhu, Xiaoyu; Nie, Ting; Lu, Fengxia; Bie, Xiaomei; Lu, Yingjian; Trouth, Frances; Lu, Zhaoxin (Frontiers in Microbiology, 2018)
Pullulanase plays an important role in the bio-fuel, animal feed, and food industry as a starch hydrolysis enzyme. Compared to other currently used methods of pullulanase production, synthesis using B. subtilis is more safe and easily applicable. However, the yield of pullulanase from B. subtilis is low and cannot match industrial requirements. Therefore, it is necessary to improve the yield of pullulanase by multiple methods. In this study, we mined ten highly active promoters from B. subtilis based on transcriptome and bioinformatic analysis. These individual promoters and their combinations were used to improve the yield of pullulanase in B. subtilis BS001. Four recombinant isolate strains with new promoters (Phag, PtufA, PsodA, and PfusA) had higher enzyme activity than that of control (PamyE). The strain with PsodA+fusA (163U/ml) and strain with PsodA+fusA+amyE (336U/ml) had the highest activity among the dual- and triple-promoter constructs in flasks, which was 2.29 and 4.73 times that of the strain with PamyE, respectively. Moreover, the activity of the strain with PsodA+fusA+amyE could be maximized to 21.9 times (1555 U/ml) that of the flask grown strain with PamyE by using a 50-liter fermenter. Our research indicates that the four strong promoters and their combinations that were mined from transcriptome data could increase the yield of pullulanase reliably and in quantities better suited for industrial application.